2019
DOI: 10.2174/1574885514666190212113754
|View full text |Cite
|
Sign up to set email alerts
|

Drug/Vehicle Impacts and Formulation Centered Stratagems for Enhanced Transdermal Drug Permeation, Controlled Release and Safety: Unparalleled Past and Recent Innovations-An Overview

Abstract: : Transdermal drug delivery systems (TDDS) are one of the fascinating unconventional drug delivery systems offering plentiful advantages of which patient compliance is of paramount importance. However, as a matter of fact, the transdermal delivery of drug molecules is absolutely a tedious job which is precisely influenced by a number of factors including penetration barrier properties of the skin, drug characteristics formulation allied issues, etc. Over the years, innumerable tremendous efforts have been made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…Therefore, to enhance transdermal delivery, it may be necessary to employ various enhancement techniques such as chemical or physical methods or by using nanocarrier systems. Nanocarrier systems such as nanoparticles or nanovesicles possess advantages over the other methods as they promote transdermal permeation without affecting the skin's structure (Williams and Barry 2004;Manickam et al 2019). Although nanoparticles have shown some success in transdermal delivery, the tough SC layer is still a challenging barrier (Nair Rajesh Sreedharan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to enhance transdermal delivery, it may be necessary to employ various enhancement techniques such as chemical or physical methods or by using nanocarrier systems. Nanocarrier systems such as nanoparticles or nanovesicles possess advantages over the other methods as they promote transdermal permeation without affecting the skin's structure (Williams and Barry 2004;Manickam et al 2019). Although nanoparticles have shown some success in transdermal delivery, the tough SC layer is still a challenging barrier (Nair Rajesh Sreedharan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported optimising drug-free nanoethosomes by altering the lipid concentration, ethanol content, and sonication time (Nair Rajesh Sreedharan et al 2020). Furthermore, it is suggested that the nanosize particles are capable of transporting drugs across the skin layers; therefore, we aimed to limit the ethosomal size below 100 nm (Raju Y et al 2017;Manickam et al 2019). Particle size was found to increase with increasing concentrations of SPC and ethanol.…”
Section: Formulation Of Curcumin Nanoethosomesmentioning
confidence: 99%